Air‐In‐Water Emulsion Solely Stabilized by Gelatin Methacryloyl and Templating for Macroporous Nanocomposite Hydrogels. Issue 9 (3rd April 2019) - Liu, Sa; Jin, Min; Chen, Yunhua; Teng, Lijing; Qi, Dawei; Ren, Li
Abstract: Concentrated emulsions are extremely interesting templates to produce macroporous hydrogels for 3D cell culturing and tissue regeneration. However, organic solvents have been intensively used as dispersing phases to prepare these emulsions, which could involve considerable efforts to purify the scaffolds to minimize their toxicity to cells. In this contribution, air‐in‐water emulsions without involving any organic solvents, stabilized solely by gelatin methacryloyl are reported. The emulsions can serve as promising templates to produce highly macroporous hydrogels, and the incorporation of Laponite clay is able to regulate the pore surface morphology and lead to significant increase of compressive modulus of the nanocomposite hydrogels. Furthermore, remarkable cell proliferation and increase of alkaline phosphatase activity are demonstrated in the macroporous nanocomposite hydrogels, indicating their great capability of promoting osteogenesis in the absence of osteoinductive factors. Abstract : Air‐in‐water emulsions solely stabilized by gelatin methacryloyl are developed and the emulsion templates are utilized to create promising macroporous nanocomposite hydrogels . Promising mechanical reinforcement, cell proliferation, and significant increase of alkaline phosphatase activity are shown in hydrogels incorporated with Laponite clay, indicating the capabilities of promoting osteogenesis of the hydrogels in the absence of osteoinductive factors.